Староверие Литвы в 1944-1953 гг.: «новый курс» советских властей, деятельность ВСС, изменение численности поморских общин - Paaver-Potashenko, Mari-Liis (Acta Neophilologica, 2022)
This article offers an art analysis of the collection of icons by the Estonian icon painter Pimen Sofronov housed in the Monastery of Chevetogne in Belgium. Sofronov’s icons found their way to this monastery in different ways. All of the seven icons were created in the 1930s, when he taught the orthodox icon painting and worked in various places in Europe and personally acquired an abundance of new knowledge. The author examines the development of Sofronov’s artistic language during these years and discusses the European artistic and cultural context of that time, which is essential to understanding his work. Despite his acquaintance with different cultures and traditions of icon painting, Sofronov remained true to his roots as can be seen in his icons in Chevetogne. Sofronov found his own way of developing and renewing the Old Believers’ icon painting tradition. This can also be perceived as a deeper understanding of the traditional Russian Old Believer icon painting.